Сприйняття й переживання простору: берлінська та єгипетська пустелі Інґеборґ Бахман - Цибенко, Лариса; Tsybenko, Larissa (Східноєвропейський національний університет імені Лесі Українки, 2015)
У науковій розвідці художньо відтворено суб’єктивно сприйнятий і пережитий простір пустелі. Дослідження виконано за допомогою феноменологічних підходів до простору, у центрі уваги яких – сутність людської екзистенції. Предмет вивчення – два тексти Інґеборґ Бахман: промова з нагоди вручення премії ім. Бюхнера «Місце для випадків» та остаточна редакція незакінченого роману «Книга Франци».Portrayal of percepted and experienced space takes an especial place in Inheborh Bahman’s creative work. Phenomenological methods of research are suitable for the analysis, the main method is perception of the essence of being based on the human’s experience. In our research we use the theories of Roman Inharden (thesis on literary art work as an aesthetic subject and conception of space orientation); of Kurt Levin (methodology of topological description of space taking into account the situation in which it is percepted or experienced) and of Moris Merlo-Ponti (teaching in «reversibility» of space while percepting it). Two texts of Inheborh Bahman are studied in our research: a published speech for the presentation of Buchner reward «The place for fortuity» and an unfinished novel «The book of Frants», she worked on them simultaneously. The object of our research is the peculiarities of the art depiction of a desert as perceived and experienced «inner» space. At the beginning of the work Bahman studies and represents the space of a desert in a single complex as space of solitude and death (Berlin and Egyptian deserts), then she separates and contrasts. As a result, the space of a desert transforms into the space of liberation and possible recovery. Sahara loses the character of danger, it is perceived as an open, peaceful and free landscape.
The Perception and Feeling of Space: Berlin and Egyptian Deserts of Inheborh Bahman
Keywords: феноменологія простору; сприйняття та переживання простору; простір пустелі; промова «Місце для випадків»; роман «Книга Франци»; phenomenology of space; perception and experience of space; space of desert; Inheborh Bahman; speech «Place for fortuity»; novel «Book of Frants»; Інґеборґ Бахман